Intensitas Kerusakan pada Beberapa Varietas Tebu Akibat Serangan Penggerek Pucuk Tebu (Scirpophaga nivella intacta) setelah Aplikasi Zat Pemacu Kemasakan Isoprophylamine Glyphosate - Sudarsono, Hamim; Sunaryo, Sunaryo; Saefudin, Saefudin (Jurnal Penelitian Pertanian Terapan, 2011)
Isoprophylamine glyphosate, a common herbicide, is widely used as a sugarcane ripener to hasten maturation and to increase sugar yield in many countries. The ripener also alter the physiology of sugarcane that might consequently affect the development of the sugarcane shoot borer, Scirpophaga nivella intacta Snell (Lepidoptera: Pyralidae). This research studied the effect of isoprophylamine glyphosate on the intensity of S. nivella intacta attacks on several cultivars of sugarcane. Results of the experiment showed that varieties of sugarcanes responded differently after application of isoprophylamine glyphosate. The percentages of damaged nodes by S. nivella intacta were higher following the application of the ripener on GM 21 and RGM 97-10167 cultivars. Conversely, the damage nodes were lower on RGM 97-8752 and RGM 97-10120 at 20-30 days after the application of the ripener. Out of four tested cultivars, GM 21 was in general the most susceptible to the attacks of the sugarcane shoot borer. On the other side, there was an indication that cultivar RGM 97-10120 applied with isoprophylamine glyphosate had the lowest damage level by S. nivella intacta. The cultivar could be further investigated to study wether it has the potential as a better cultivar against S. nivella intacta when isoprophylamine glyphosate is applied as the cane ripener. Keyword: ripener, soprophylamine glyphosate, Scirpophaga nivella intacta, sugarcane